2011
DOI: 10.4236/fns.2011.24053
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Organ Distribution of Feed Introduced Plasmid DNA in Growing or Pregnant Rats

Abstract: Fragments of DNA present in food and feed are taken up by the gastrointestinal tract (GIT) of mammals. The extent of uptake varies according to organism, study design and DNA source. This study explores the hypothesis that actively growing, as well as pregnant rats, are more likely to take up DNA from the GIT than mature animals due to the high demand for nutrients for tissue and organ development. Plasmid DNA (pDNA) was added to standard feed for growing, and pregnant rats. The young rats received one pDNA (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…Walsh et al (2011) detected transgenic DNA (cry1Ab) and protein only in the GIT digesta and not in the tissues (kidney, liver, muscle, heart or blood) of pigs fed Bt MON810 maize. Grønsberg et al (2011) reported that the low level of plasmid DNA introduced in feed was transiently detected in organs of young, growing rats; however, there was no indication of increased DNA uptake levels in the GIT of growing rats (Grønsberg et al, 2011). Chowdhury et al (2003) detected endogenous gene segments of maize (zein, 242 bp; invertase, 226 bp; rubisco, 1028 bp) in the GIT contents of pigs fed Bt and non-transgenic maize.…”
Section: Discussionmentioning
confidence: 99%
“…Walsh et al (2011) detected transgenic DNA (cry1Ab) and protein only in the GIT digesta and not in the tissues (kidney, liver, muscle, heart or blood) of pigs fed Bt MON810 maize. Grønsberg et al (2011) reported that the low level of plasmid DNA introduced in feed was transiently detected in organs of young, growing rats; however, there was no indication of increased DNA uptake levels in the GIT of growing rats (Grønsberg et al, 2011). Chowdhury et al (2003) detected endogenous gene segments of maize (zein, 242 bp; invertase, 226 bp; rubisco, 1028 bp) in the GIT contents of pigs fed Bt and non-transgenic maize.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the actions of Bt toxins (extracted from Bacillus thuringiensis ) are subject to more controversy than when Bt plants were first developed [ 19 ]. Transgenic DNA and proteins may pass through mammalian or avian gastrointestinal tracts [ 20 22 ], as well as through animals that consume them, where transgenic DNA and proteins circulate in the blood and internal organs [ 23 ]. The propagation effect of a disturbance at the trophic level to other levels of the food chain may also be occurring.…”
Section: Introductionmentioning
confidence: 99%
“…Control rats received the same pellets, but without DNA. Previous studies have shown that the feed source is free of DNA and that DNA mixed into the pellet does not degrade or lose its ability to transform bacteria over a 72 h incubation period at RT [ 56 ].…”
Section: Methodsmentioning
confidence: 99%